2014
DOI: 10.1177/1756285614555335
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences for disease-modifying drugs in multiple sclerosis therapy: a choice-based conjoint analysis

Abstract: Our results suggest that route of administration and treatment frequency play an important role in the patients' preference for a given DMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 16 publications
4
69
0
7
Order By: Relevance
“…The same result was not observed in the USA 6 , where patients had a strong preference for oral drugs. A German study showed that patients prefer oral drugs over injectable ones if the administration of the pills was once a day 7 .…”
Section: Discussionmentioning
confidence: 99%
“…The same result was not observed in the USA 6 , where patients had a strong preference for oral drugs. A German study showed that patients prefer oral drugs over injectable ones if the administration of the pills was once a day 7 .…”
Section: Discussionmentioning
confidence: 99%
“…DCEs have been used previously to study preferences for MS treatments [Johnson et al 2009;Shingler et al 2013;Utz et al 2014;Wicks et al 2015;Wilson et al 2014Wilson et al , 2015. Shingler and colleagues assessed patient preference for features of injection devices and treatment efficacy, showing that while efficacy is of primary importance, device attributes can play an important role in patient preference.…”
Section: Introductionmentioning
confidence: 99%
“…Однозначно, врач совмест-но с пациентом должен стремиться к сохранению высокой приверженности к терапии, для чего при-меняемый препарат должен быть и эффективен, и хорошо переноситься пациентом. Безусловно, и путь введения препарата оказывает влияние на тера-певтическую комплаентность -применение пер-оральных форм ПИТРС является более привлека-тельным для пациента в отличие от форм инъекци-онных [39].…”
Section: место дмф в современной терапии рсunclassified